2019
DOI: 10.15611/eada.2019.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Modelling factors connected with the effect of international migration for security and economy

Abstract: This article concerns research conducted on the casual connections between modern global migratory processes and basic socioeconomic and safety indexes for countries around the world countries. On the basis of new official dataset there was developed a cluster model of countries distributed according to the basic indicators which characterize migratory streams (emigration/ immigration), safety and macroeconomic indexes, related to the international migration. It is established that, in general, people are movi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Same author used multivariate analysis of non-metric data in evaluating the generational perception of social characteristics (Stanimir, 2020b). K. Berezka and O. Kovalchuk (2019) used factor analysis and principal components analysis to study the causal links of modern global migration processes with basic socio-economic and security indicators for the world. P. Boedeker and N. T. Kearns (2019) investigated predictive classification and found that in some cases linear discriminant analysis works better than other prediction methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Same author used multivariate analysis of non-metric data in evaluating the generational perception of social characteristics (Stanimir, 2020b). K. Berezka and O. Kovalchuk (2019) used factor analysis and principal components analysis to study the causal links of modern global migration processes with basic socio-economic and security indicators for the world. P. Boedeker and N. T. Kearns (2019) investigated predictive classification and found that in some cases linear discriminant analysis works better than other prediction methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stanimir A. methods of a multivariate analysis of non-metric data in evaluating the generational perception of social characteristics [9]. Berezka K., Kovalchuk O. used factor analysis and principal components analysis to study the causal links of modern global migration processes with basic socio-economic and security indicators for the world [4]. Boedeker P., Kearns N. T. investigated the predictive classification and found that in some cases linear discriminant analysis works better than other prediction methods [10].…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%